2019
DOI: 10.1055/s-0039-1696910
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Its Response to Supplementation as “Stoss Therapy” in Children with Cyanotic Congenital Heart Disease Undergoing Open Heart Surgery

Abstract: Background Data from many studies suggest that patients with congenital heart disease are vitamin D (vitD) deficient. Following cardiac surgery as a result of intraoperative institution of cardiopulmonary bypass (CPB), serum vitD levels become even low. This may affect postoperative convalescence in terms of mechanical ventilation, inotropic support, infection, and so forth. Objective We intended to study the prevalence of vitD deficiency pre and post cardiac surgery and the effect of vitD supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…Comparable findings were presented in the VITdAL-ICU trial ( n = 475), where 25% hypercalciuria rates were documented pre- and post-study drug administration in critically ill adults receiving either placebo or a 540,000-IU cholecalciferol loading dose [ 23 ]. Similar results were evident in the study by Sahu and colleagues where the average perioperative urine calcium to creatine ratios were reported to be similar or potentially lower in the loading dose arm (2.1 vs. 1.0, p = 0.16) [ 27 ]. In the critical care setting, hypercalciuria may not represent a great biomarker of excess vitamin D given the high prevalence of acute kidney injury and medications (e.g., furosemide) known to promote urinary calcium loss.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Comparable findings were presented in the VITdAL-ICU trial ( n = 475), where 25% hypercalciuria rates were documented pre- and post-study drug administration in critically ill adults receiving either placebo or a 540,000-IU cholecalciferol loading dose [ 23 ]. Similar results were evident in the study by Sahu and colleagues where the average perioperative urine calcium to creatine ratios were reported to be similar or potentially lower in the loading dose arm (2.1 vs. 1.0, p = 0.16) [ 27 ]. In the critical care setting, hypercalciuria may not represent a great biomarker of excess vitamin D given the high prevalence of acute kidney injury and medications (e.g., furosemide) known to promote urinary calcium loss.…”
Section: Discussionsupporting
confidence: 86%
“…Fortunately, multiple adult and pediatric studies have shown that it is possible to safely significantly raise 25OHD levels over a 48-to 72-h time period using a single large age or weight-based enteral load of cholecalciferol (50,000-400, [42,[46][47][48], without any signs of toxicity. In addition to the aforementioned study by Sahu and colleagues, we have confirmed these findings in our recent VITdAL-PICU pilot trial using a loading dose of vitamin D (10,000 IU/kg, maximum 400,000 IU) in critically ill children (NCT02452762) [27].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations